2020
DOI: 10.1590/0034-7167-2019-0123
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between functional capacity, performance and symptoms in hospitalized patients with heart failure

Abstract: Objectives: to evaluate the prevalence of symptoms in heart failure patients and to investigate the relationship between symptoms, functional capacity and performance. Methods: cross-sectional study, developed at a hospital specializing in cardiology. The sample (n=170) consisted of patients with heart failure, assessed by means of a sociodemographic form, New York Heart Association Functional Class, Edmonton Symptom Rating Scale and Karnofsky Physical Performance Scale. Analyzes were performed using Spearman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
5
6
0
6
Order By: Relevance
“…Correlation analysis between anxiety and depression showed positive relationship. It was consistent with previous studies which revealed that the higher anxiety associated with the higher depression among patients with HF [5], [20], [24]. According to multivariate regression results in this study, anxiety was also become significant predictor of depression and vice versa.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Correlation analysis between anxiety and depression showed positive relationship. It was consistent with previous studies which revealed that the higher anxiety associated with the higher depression among patients with HF [5], [20], [24]. According to multivariate regression results in this study, anxiety was also become significant predictor of depression and vice versa.…”
Section: Discussionsupporting
confidence: 93%
“…According to multivariate regression results in this study, anxiety was also become significant predictor of depression and vice versa. Anxiety leads to moments of self-exploration and contributes to depressive symptoms [24]. This is supported by previous studies that explain the pathophysiological relationship between those mental disorders.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Concerning exercise performance, day0 SSE is accompanied by largely reduced aerobic power output compared to baseline. These results corroborate the common opinion that sympathetic overactivation is associated with poor performance in connection with overreaching and overtraining [ 8 ] or in chronic heart failure patients [ 39 , 41 , 42 , 43 ]. The precise mechanism underlying decreased performance at higher sympathetic outflow is not completely clear [ 44 ]; nevertheless, it is obvious that adaptation to exercise upon sympathetic overactivation at its onset is compromised [ 12 ] and that interplay of simultaneous sympathetic overactivation and parasympathetic decline may have a role.…”
Section: Discussionsupporting
confidence: 89%
“…Autora correspondente: Janaína Mengal Gomes Fabri. E-mail: janamgfabri@gmail.com Editora Científica: Cristiane Helena Gallasch; Editora Associada: Mercedes Neto O escasso número de publicações nacionais e internacionais acerca das intervenções da espiritualidade na cardiologia e o fato de as doenças cardiovasculares permanecerem, há 15 anos, no topo das maiores causas de óbitos no mundo ratificam a importância do desenvolvimento de pesquisas que promovam estratégias potencializadoras de adesão ao tratamento e, assim, atuem na promoção de hábitos saudáveis, na prevenção de agravos e na reabilitação [1][2][3][4][5][6][7][8][9] .…”
Section: ____________________unclassified